Association Between Thyroid Dysfunction And Reproductive Hormone Profiles In An Iraqi Population - Yasameen Hameed Jasim (Fakultas Pertanian, 2026)
Thyroid dysfunction can disrupt endocrine and metabolic processes, including reproductive hormone regulation, yet population-specific data remain scarce. This cross-sectional study investigated the relationship between thyroid dysfunction and reproductive hormone profiles in an Iraqi population. The study involved 210 participants divided into three groups: 70 hyperthyroid patients, 70 hypothyroid patients, and 70 age- and sex-matched healthy controls, including both males and females. Serum levels of TSH, FT3, FT4, testosterone, oestrogen, LH, FSH, and prolactin were assessed using enzyme immunoassay methods. Distinct thyroid hormone patterns validated group classification. Hypothyroid patients exhibited decreased FT3 and FT4 levels with elevated TSH, whereas hyperthyroid patients showed increased FT3 and FT4 with suppressed TSH. Significant differences were also observed in sex steroid hormones. Testosterone and oestrogen levels were significantly lower in hypothyroid patients compared with hyperthyroid patients and controls. Prolactin concentrations were higher in hypothyroid patients than in hyperthyroid patients, though still lower than in healthy individuals. No significant differences were found in LH and FSH levels across groups. Additionally, hypothyroid patients had a higher BMI than the other groups. Overall, the findings suggest that thyroid dysfunction, particularly thyrotoxicosis, affects sex steroid hormones and prolactin secretion, while gonadotropin levels remain relatively unchanged, emphasizing the role of thyroid hormones in reproductive endocrinology.